CLASSIFICATION OF AFFIXES ACCORDING TO VARIOUS CRITERIA (Modern education and development, 2025)
The topic “Classification of Affixes According to Various Criteria” explores the systematic categorization of affixes—morphemic units attached to roots or stems—in English. It focuses on different classification principles such as position in word structure (prefixes, suffixes, infixes, circumfixes), function in part-of-speech transformation (e.g., nominal, verbal, adjectival affixes), origin (native vsborrowed), semantic contribution (e.g., negation, intensity, repetition), and usage(productive vs non-productive). Understanding these classifications is essential forstudying word formation, enriching vocabulary, and analyzing morphologicalprocesses in English linguistics.